PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS HIERARKI KONSEP POKOK BAHASAN LARUTAN PENYANGGA - Safira, Melani; Susilawati, Susilawati; Amran, Elva Yasmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This Research aims to develop Student Activities Worksheets Based on Hierarchy of Concept on the buffer solution subject valid based on the feasibility aspect of content, language, serve and graphic. The type of this research is research and development (R and D) with reference to the development process of 4-D model. The subject of this research is student activities worksheets based on hierarchy of concept. Instrument of data collection are validation given to three validators, and from analysis data obtained by the validity of aspect of content, aspect of language, aspect of serve, and aspect of graphic are 93,45%, 91,67%, 95,83%, dan 89,58% with valid category. Student activities worksheets which validated by the validators tested to 30 students and get response result with percentage of 88,07% with positive category, and assessed the praticality by three teachers and get response result with percentage of 95,28% with very practical category. Based on the result of data analysis can be concluded that student activities worksheets based on hierarchy of concept that produced is valid and can be used for the subject buffer solution.Keywords : Buffer Solution, Student Activities Worksheet, Hierarchy of Concept